Volunteer management in information centers with special reference to the Zimbabwe Military Museum (ZMM) - Mukwidzi, Nyasha (Midlands State University, 2017)
The overall aim of the research was to provide and establish the guidelines which were supposed to be used by the museum in managing volunteers. The research was based on four main objectives that included the following. Examining how the museum plans for its volunteer programs, assessing the methods used by the museum in recruiting volunteers, assessing how the museum motivates its volunteers as well as to determine the barriers that impede people into volunteering in museums.Using the Volunteer Management Cycle as the theoretical framework of this study, it stated that volunteer management in information centres should consists of five major phases that include planning, recruitment, training, supervision and recognition. However this study examined the management of volunteers at the Zimbabwe Military Museum (ZMM). In achieving the aim of the research, the research adopted a case study research design. Thus the study employed interviews and questionnaires to collect data from the respondents. This also led to the understanding that volunteer management in Zimbabwe was not yet a well-established and not well appreciated phenomenon evidenced by lack of a number of volunteer management tools. These included the lack of a volunteer policy, lack of a volunteer manager, lack of employed volunteer recruitment tools and also lack of strategic motivation and recognition process. On the other hand the research found out that volunteers are being obstructed into volunteering at the museum due to a number of factors. These factors included the military nature of the museum, lack of planning and formulation of volunteer policies as well as lack of publicizing and marketing the practices of the museum to the public. Recommendations were also given which included the need to come up with a viable volunteer policy, the need to employ a volunteer manager and also to encourage international volunteers the museum should also work on publicizing the museum so as to correct the misconceptions about the nature of the museum.